'It's kinda bad, honestly': Australian students' experiences of relationships and sexuality education. Issue 6 (15th September 2020) - Waling, Andrea; Bellamy, Roz; Ezer, Paulina; Kerr, Lucille; Lucke, Jayne; Fisher, Christopher
Abstract: Relationships and sexuality education for young people in Australia and elsewhere is a controversial topic. Numerous studies in Australia have focused on curriculum, policy, teachers, schools, sexting and other behaviours, and knowledge regarding sexually transmitted infection (STI)/human immunodeficiency virus (HIV) and pregnancy prevention. Few large-scale national studies have engaged with young people about what they want out of their sex education, and what they suggest would be most valuable for future programs in Australia. Data for the study included qualitative comments about experiences of sex education ( n = 2316) provided in a national survey of adolescent sexual health. An initial thematic inductive analysis identified comments falling into two dominant themes: positive and negative experiences of their sex education. Results indicate that young people in Australia are articulate and understanding of the gaps in their sex education. A majority of comments highlighted negative experiences. These comments primarily discussed issues of delivery (timing, environment, person) and content quality (comprehensiveness). A minority highlighted positive commentary also around delivery (environment, person) and content quality (comprehensiveness). The findings of this study illuminate contemporary adolescent concerns regarding their experiences of education. Understanding these experiences can inform future curriculum development, teacher training and the design and implementation of policy.